Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Pengawasan Keuangan Dan Pembangunan (BPKP) Perwakilan Provinsi Sulawesi Selatan - Muhammad Natsir Mallawi; Ita Sila (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Companies or agencies/organizations must have quality human resources (HR) to achieve good performance results so that the company or agency/organization can achieve its goals. One way for companies/agencies/organizations to improve employee performance is by paying attention to the employee's work environment in the office to create a comfortable atmosphere for employees in carrying out their work. This research aims to find out how the work environment influences employee performance. This research used a simple random sampling technique (simple random sampling), with a sample of 34 respondents from the Office of the Financial and Development Supervisory Agency (BPKP) representing the province of South Sulawesi. This research uses quantitative, descriptive methods and the analysis used in this research is simple linear regression analysis. The results of the descriptive analysis in this research show that from the analysis of the coefficient of determination the R-square value is 0.380, meaning that 38% of employee performance is influenced by the work environment, the remaining 62% is influenced by variables other than the work environment. Likewise, the results of the t test (hypothesis) show that the t-count is greater than the t-table (4.433 > 1.691) and the significance is smaller than 0.05 (0.000 < 0.05), then H0 is accepted (there is an influence of variable Y). Thus, companies/agencies/organizations need to consider the work environment as a factor that can improve performance.